Perilaku Pengendara Sepeda Terhadap Keselamatan di Jalan - Danang Febrianto; Dewanti Dewanti; Imam Muthohar (Program Studi Sarjana Teknik Sipil Universitas Internasional Batam, 2021)
In the middle of social distancing imposed by the government of Indonesia to reduce the spread rate of COVID-19 virus, the use of bicycles has emerged as a new trend in various cities in Indonesia, one of which is the Special Region of Yogyakarta. However, the increasing growth of bicycle users are also directly proportional to the data on cyclists' accidents. One of the factors causing high number of accidents on cyclists is the human factor. The purpose of this study was to analyze the behavior of cyclists in the Special Region of Yogyakarta. The data used in the study were granted from questionnaires and field observations of cyclists. Descriptive analysis is used to describe the characteristics and behavior of cyclists. Samples were taken using purposive sampling method with a questionnaire resulting the number of respondents as many as 362 cyclists. The results showed that the behavior of cyclists in Special Region of Yogyakarta were quite good, but there are still a lot of cyclists that do not know about regulations governing road cycling safety. It was found that the use of safety equipment does not present traffic compliance.